Simulation studies of vibration isolation using electromagnetic damper - Mohd Fazli Mohd Yusoff; Ahmad Mujahid Ahmad Zaidi; Saiddi Ali Firdaus Ishak; Mat Kamil Awang; Muhamad Faiz Md Din (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper presents the review of electromagnetic damper as a vibration/isolation material. A bunch of articles about vibration and suspension system was reviewed and the key factors that contribute to electromagnetic damper was identified. Electromagnetic damper has been given special attention from many researchers and thus being among the important research area in vibration system. Vibration concept of electromagnetic damper has been elucidated by referring to several paper that demonstrate the usage of electromagnetic damper. Finite element magnetic method (FEMM) software has been used in order to identify the best configuration of geometry in the system. A simulation in Matlab was done by considering a quarter car model with a theoretical value from the Faraday’s Law equation involved in electromagnetic damper. The slotted and cylindrical geometry configurations have been simulated using FEMM and the result clearly shows that the slotted configuration has a better effect on the electromagnetic damper system.